Arrival mode and triage evaluation in an emergency department cohort of patients with syncope: the ADDRESS study - Filippo Numeroso; Ivo Casagranda (Emergency Care Journal)
In a cohort of 378 emergency department (ED) syncopal patients, we evaluated the arrival mode and the efficacy of triage evaluation in predicting cardiac syncope, acute underlying diseases, and the need for admission. Less than half of patients (48.4%) arrived in the ED with emergency medical services (EMS), and in a small minority of cases (12.4%), an electrocardiogram (ECG) was performed at the triage, even in cases of cardiac syncope (44% and 8%, respectively). Most patients (67.4%) received a white, green, or blue code; the triage priority code was associated with the presence of cardiac syncope and acute underlying diseases when indicative of high severity (i.e., red or orange), with a high negative predictive value (95% and 81%, respectively) if lower. Triage priority was also associated with the need for admission when indicative of a high care complexity (i.e., orange, red, or blue), with a high negative predictive value if lower. To ensure a rapid evaluation of cases at higher risk, it would be appropriate to increase the number of patients transferred to ED by EMS and the execution of the ECG at triage. To reduce unnecessary admissions, the role of ED triage should be valued, as it is able to identify patients without cardiac syncope or acute underlying diseases, especially in the case of a high care complexity but a low severity code (blue).